Duration and Dosage of Opioids After Spine Surgery: Implications on Outcomes at 1 Year. Issue 15 (1st August 2020) - Hills, Jeffrey M.; Carlile, Catherine R.; Archer, Kristin R.; Wick, Joseph B.; Butler, Marjorie; Daryoush, Joshua; Khan, Inamullah; Call, Richard; Devin, Clinton J.; Pennings, Jacquelyn S.
Abstract : Study Design: Longitudinal Cohort Study Objective: The aim of this study was to determine whether duration of postoperative opioids is associated with long-term outcomes, and if initial postoperative opioid dosage is associated with opioid cessation after spine surgery. Summary of Background Data: Preoperative opioid use is associated with poor outcomes, but little evidence exists regarding the implications of opioid dosage and duration after spine surgery. Methods: Data from our state's prescription drug database was linked to our prospective clinical spine registry to analyze opioid dispensing and outcomes in elective surgical spine patients between 2010 and 2017. Patients were stratified based on preoperative chronic opioid use and multivariable regression was used to assess associations between duration of postoperative opioids and outcomes at one year, including satisfaction, chronic opioid use, and meaningful improvements in pain, disability, and quality of life. In a secondary aim, a Cox proportional hazards model was used to determine whether initial postoperative opioid dosage was associated with time to opioid cessation. Results: Of 2172 patients included, 35% had preoperative chronic opioid use. In patients without preoperative chronic opioid use, a postoperative opioid duration of 31 to 60 days was associated with chronic opioid use at 1 year (adjusted odds ratio [aOR]: 4.1 [1.7–9.8]) and no meaningful improvement in extremity pain (aOR: 1.8 [1.3–2.6]) or axial pain (aOR: 1.6 [1.1–2.2]); cessation between 61 and 90 days was associated with no meaningful improvement in disability (aOR: 2 [1.3–3]) and dissatisfaction (aOR:1.8 [1–3.1]). In patients with preoperative chronic opioid use, postoperative opioids for ≥90 days was associated with dissatisfaction. Cox regression analyses showed lower initial postoperative opioid dosages were associated with faster opioid cessation in both groups. Conclusion: Our results suggest that a shorter duration of postoperative opioids may result in improved 1-year patient-reported outcomes, and that lower postoperative opioid dosages may lead to faster opioid cessation. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the textImplications of dosage and duration of opioids after spine surgery were assessed. Our results suggest that a shorter duration of postoperative opioids may result in improved 1-year patient reported outcomes, and that lower postoperative opioid dosages may lead to faster opioid cessation.